The effect of dissolved natural organic matter on adsorption of phenolic compounds on suspended sediments. Issue 22 (2nd October 2022) - Chen, Yuyun; Duan, Ting; Li, Wei; Zhang, Junqin; Dong, Yanxia; Zhou, Yiqiang; Zhou, Yifan
ABSTRACT: Phenolic compounds have caused different degrees of negative impacts in aquatic environment. Amino acids, humic acids and carbohydrates are the three dominant types of dissolved natural organic matter (DNOM) in natural water bodies. In this research, the influences of dissolved natural organic matter (DNOM) on the adsorption behaviors of phenol, 2, 4-dichlorophenol (DCP) and 2, 4, 6-trichlorophenol (TCP) in Weihe River suspended sediment were studied by using DL-alanine, fulvic acid and glucose as the representatives of the three types of DNOM. The results of batch adsorption experiments showed that, without DNOM, Langmuir and Freundlich had good fitting effects on the three phenolic compounds and their maximum adsorption capacities were 21.580, 27.768 and 24.758 mg/kg respectively. The presence of amino acids increased adsorption capacities of the phenol and TCP on suspended sediments by approximately 13.84% and 11.56% respectively. The existence of fulvic acid and glucose positively affected the adsorption of phenol, DCP and TCP on suspended sediment. The isothermal adsorption in the coexistence of different DNOM were more consistent with the nonlinear adsorption. Other influence factors including pH, ionic strength and temperature can influence the adsorption behavior to different extents. The impact of dissolved natural organic matter (DNOM) on adsorption should be fully considered when mastering environmental migration and transformation behaviors of phenolic compounds in water-sediments environment. GRAPHICAL ABSTRACT: UF0001